Blood results in clinical practice - Basten, Graham (Keswick : M & K Update, 2013)
This book was written after feedback suggested that stories and analogies were very helpful to students wanting to remember blood tests and their implications. For this reason each section, where appropriate, contains an analogy, in addition to an overview of the relevant anatomy, physiology and biochemistry. The book links tests and conditions, and gives strategies for clinical practice using simple language. It will be useful as a supplementary text for those studying nursing, healthcare and medicine. It will also provide a quick-reference handbook for working healthcare professionals. Finall.
AfterwordFurther reading and references; Index.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on September 17, 2018).
eBooks on EBSCOhost
Keywords: Blood -- Analysis; Blood -- Examination; Phlebotomy; Blood; Blood; Blood Chemical Analysis; Blood Specimen Collection; Bloodletting; Sang -- Analyse; Sang -- Examen; Saignée.; Sang; blood (animal material); MEDICAL -- Clinical Medicine; SCIENCE -- Chemistry -- Clinical; Blood; Blood -- Examination; Blood -- Analysis; Phlebotomy